Combined application of single-energy metal artifact reduction and reconstruction techniques in patients with Cochlear implants - Fanqin Wei; Jiahui Li; Chunxiang Zhou; Yun Li; Xianren Wang; Bixue Huang; Qiyang Sun; Guanxia Xiong (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The purpose of this study was to develop an effective method of reducing metal artifacts in cochlear implant (CI) electrodes. Methods The temporal bones of 30 patients (34 ears) after CI were examined with 320-detector row computed tomography, which was evaluated by two senior radiologists using a double-blind method. Noise, artifact index, signal-to-noise ratio, and the subjective image quality score were compared before versus after using single-energy metal artifact reduction (SEMAR). The electrode position, single electrode visibility, and electrode count were evaluated using SEMAR combined with either multi-planar reconstruction (MPR) or maximum intensity projection. Results The two radiologists’ measurements had good consistency. SEMAR significantly reduced the image noise and artifacts index and significantly improved the signal-to-noise ratio and subjective image quality score (P < 0.01). The combination of SEMAR with MPR was conducive to accurate assessment of electrode position and single-electrode visibility. The combination of SEMAR with MIP facilitated accurate and intuitive matching of the assessed electrode count with the number of electrodes implanted during the operation (P = 0.062). Conclusion SEMAR significantly reduces metal artifacts generated by CI electrodes and improves the quality of computed tomography images. The combination of SEMAR with MPR and maximum intensity projection is beneficial for evaluating the position and number of CI electrodes.